PERANAN AUDIT MANAJEMEN DALAM MENILAI EFEKTIVITAS DAN EFISIENSI PELAYANAN TERHADAP PASIEN DI DEPARTEMEN BEDAH RUMKITAL DR. RAMELAN SURABAYA - Yunita, Ayu Puspa; Bayangkara, I.B.K. (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACT,This study aims to determine,the role of, management audits in assessing the effectiveness and, efficiency of service to patients  in the surgical,  departement Rumkital Dr. Ramelan Surabaya. This research is  a  case  study  with qualitative, descriptive method, throught interview, observation and questionnaire. The effectiveness and, efficiency, of,services to patients is analyzed and,evaluated by comparing the, criteria, causes, effects and providing recommendations. Based on the result of, the research, it can be conclude that the activity    or service activity, in Departement of Surgery has been run  efficiently  but not  yet effective because the, waiting time of elective surgery  of spine  surgery  patient not yet in accordane with predefined, time standard.